2022
DOI: 10.1126/sciadv.abo6693
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and bulk flow of amino acids mediate calcium waves in plants

Abstract: In plants, a variety of stimuli trigger long-range calcium signals that travel rapidly along the vasculature to distal tissues via poorly understood mechanisms. Here, we use quantitative imaging and analysis to demonstrate that traveling calcium waves are mediated by diffusion and bulk flow of amino acid chemical messengers. We propose that wounding triggers release of amino acids that diffuse locally through the apoplast, activating the calcium-permeable channel GLUTAMATE RECEPTOR-LIKE 3.3 as they pass. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…GLR1.2 and GLR1.3 are positive regulators of JA biosynthesis upon cold stress [54]. As seen, GLRs mediating [Ca 2+ ] cyt elevation are universal positive regulators of JA production under various biotic and abiotic stresses, although one study also showed that GLR-mediated Ca 2+ waves alone are insufficient to trigger JA signaling [55].…”
Section: Boxmentioning
confidence: 99%
“…GLR1.2 and GLR1.3 are positive regulators of JA biosynthesis upon cold stress [54]. As seen, GLRs mediating [Ca 2+ ] cyt elevation are universal positive regulators of JA production under various biotic and abiotic stresses, although one study also showed that GLR-mediated Ca 2+ waves alone are insufficient to trigger JA signaling [55].…”
Section: Boxmentioning
confidence: 99%
“…3F). The speed of this newly identified flg22 response is significantly slower compared to 200-1000 ”M/s that have been determined for systemic electrical, ROS or Ca 2+ signals propagating through vascular bundles in response to other stimuli (20)(21)(22)(23)(24)(25)(26)(27). Therefore, this value likely defines the cell-to-cell transcellular propagation velocity of PAMP triggered Ca 2+ /ROS signals.…”
Section: Collective Function Of Cbl1/cipk26 and Cpk5 Confers Synergis...mentioning
confidence: 78%
“…Here, we identified EVG1 as a stress responsive gene that repressed vascular differentiation. Upon wounding, induction of EVG1 was rapid, occurring between 10 minutes to 6 hours after cutting (Figure 1 and 6), suggesting hormones, reactive oxygen species or control by other rapid response factors such as cell wall or turgor pressure changes (Hoermayer et al, 2020;Zhang et al, 2022;Bellandi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%